(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
On behalf of the International Council for Traditional Music and Dance (ICTMD) and on my own behalf, I am pleased to congratulate you on an important event within the framework of the Festival, the publication of a special edition of the scientific journal «Proceedings of the National Academy of Sciences of the Kyrgyz Republic», which contains scientific works of scientists from different countries of the world presented at the international congress «Traditional Culture and Art: Problems of Preservation and Development».